2016
DOI: 10.1074/jbc.m115.683292
|View full text |Cite
|
Sign up to set email alerts
|

The Prodomain-bound Form of Bone Morphogenetic Protein 10 Is Biologically Active on Endothelial Cells

Abstract: BMP10 is highly expressed in the developing heart and plays essential roles in cardiogenesis. BMP10 deletion in mice results in embryonic lethality because of impaired cardiac development. In adults, BMP10 expression is restricted to the right atrium, though ventricular hypertrophy is accompanied by increased BMP10 expression in a rat hypertension model. However, reports of BMP10 activity in the circulation are inconclusive. In particular, it is not known whether in vivo secreted BMP10 is active or whether add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 35 publications
4
59
1
Order By: Relevance
“…Specific activation of latent BMP10⅐pro-domain complexes was achieved by cleavage of the pro-domain by the metalloprotease BMP1 (16). A recent study, however, reveals that the BMP10⅐pro-domain is active in multiple endothelial cells and that the ECD of BMPRII can release BMP10 from the pro-domain complex (33). Questions remain of how these very similar growth factors function differently in a tissue-specific manner, as BMP10 exhibits a unique role during cardiac development that cannot be compensated by BMP9 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Specific activation of latent BMP10⅐pro-domain complexes was achieved by cleavage of the pro-domain by the metalloprotease BMP1 (16). A recent study, however, reveals that the BMP10⅐pro-domain is active in multiple endothelial cells and that the ECD of BMPRII can release BMP10 from the pro-domain complex (33). Questions remain of how these very similar growth factors function differently in a tissue-specific manner, as BMP10 exhibits a unique role during cardiac development that cannot be compensated by BMP9 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Using mammalian cell-expressed full-length human recombinant BMP10 and ex vivo-cultured mouse right atria, we have recently demonstrated that prodomain bound BMP10 is not latent but fully active on multiple ECs. Circulating BMP10 activity can be detected, albeit at much lower levels than BMP9 [38].…”
Section: Regulation Of Bmp10mentioning
confidence: 97%
“…The prodomain remains bound to the mature ligands in circulation [14] (Figure 2A). When BMPs expressed in mammalian cells were subjected to nonreducing SDS/PAGE, a monomeric form (M-form) is present alongside the canonical disulfide-linked dimeric form (Dform) [36][37][38]. In the case of BMP9, two high-resolution crystal structures, both crystallized from mammalian cell expressed proteins and purified under native conditions, have shown that the M-form of BMP9 is in fact a non-covalently linked dimer, almost identical to the D-form ( Figures 2B and 2C) [37,39].…”
Section: Regulation Of Bmp9mentioning
confidence: 99%
“…The BMP10 procomplex was initially classified as latent based on activity tests using cultured C2C12 (myoblast) or NIH 3T3 (fibroblast) cells [124, 129]. However, the activity of the BMP10 procomplex on a variety of ECs was recently shown to approach that of the BMP10 growth factor homodimer [130]. These data suggest that surface proteins on ECs in addition to ALK1 might be important for either stabilizing the binding of the BMP10 prodomain or displacing it from the growth factor homodimer.…”
Section: Alk1 Signaling In Ecsmentioning
confidence: 99%